Immunomodulating capacity of kefir - Vinderola, Celso Gabriel (2005)
Kefir is a fermented milk produced by the action of lactic acid bacteria, yeasts and acetic acid bacteria, trapped in a complex matrix of polysaccharides and proteins. Beyond its inherent high nutritional value as a source of proteins and calcium, kefir has a long tradition of being regarded as good for health in countries where it is a staple in the diet. However, published human or animal feeding trials to substantiate this view are not numerous. The aim of this work was to determine the immunomodulating capacity of kefir on the intestinal mucosal immune response in mice and to demonstrate the importance of dose and cell viability on this response. BALB/c mice were fed with commercial kefir ad libitum (diluted 1/10, 1/50, 1/100 or 1/200) or pasteurized kefir (diluted 1/6, 1/10, 1/50, 1/100) for 2, 5 or 7 consecutive days. At the end of each feeding period, the bacterial translocation assay was performed in the liver. Small intestine structure was studied by haematoxilin-eosin staining and light microscopy. The number of IgA+ and IgG+ cells was also determined. For the functional doses chosen, cytokines (IL-2, IL-4, IL-6, IL-10, IL-12, TNF-α and IFN-γ) were determined. Kefir and pasteurized kefir were able to modulate the mucosal immune system in a dose-dependent manner. Kefir was administred 10-times more diluted than pasteurized kefir, but it induced an immunomodulation of similar magnitude, indicating the importance of cell viabilty. The results suggest that a Th1 response was controlled by Th2 cytokines induced by kefir feeding. Pasteurized kefir would induce both Th2 and Th1 responses. This is the first study in vivo regarding the mechanisms involved in the immunomodulating capacity of the oral administration of kefir containing viable or heat-inactivated bacteria at different doses.